An Uncommon Concurrence of Cytomegalovirus Retinitis and Corneal Endotheliitis in an Immunocompromised HIV-Negative Patient. (3rd April 2021) - Kao, Tzu-En; Chang, Yo-Chen; Lee, Po-Yen
ABSTRACT: Purpose : To describe a case of Cytomegalovirus (CMV) retinitis in both eyes complicated with unilateral corneal endotheliitis in an iatrogenic immunocompromised patient. Methods : A retrospective case report. Result : A 58-year-old male, on long-term immunosuppressive treatment for chronic glomerulonephritis and nephrotic syndrome. Ocular examination revealed bilateral vitritis and necrotizing retinitis and concurrent corneal endotheliitis with ocular hypertension in his left eye. The PCR result showed positivity for CMV infection by diagnostic aqueous aspiration. Vitritis/retinitis in both eyes resolved gradually after systemic valganciclovir use, and the endotheliitis in the left eye regressed after topical antiviral treatment. There was no recurrence of retinitis/endotheliitis with a maintenance dose of oral valganciclovir. Unfortunately, tractional macular hole developed in the left eye and complicated the visual outcome. Conclusion : CMV retinitis may occur in HIV-negative immunocompromised individuals, but CMV endotheliitis generally appears in the immunocompetent. It is a rare combination of CMV retinitis and endotheliitis in this patient.